(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
The study was conducted in the Department of Forensic Medicine, Government Medical College, Thiruvananthapuram. The period of the study was from January 2013 to June 2014. 50 cases were included among which 25 cases were the hanging cases that survived for varying periods before death and 25 cases were from the non-survived victims of hanging. Macroscopic and microscopic changes in the lungs, were compared to find out the changes resulting from hypoxic insult. The cases were studied in detail and are described below.